Empowerment-Based Lecturer Professional Development at State Islamic Religious Universities - Mahmud, Hilal; Abduh, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to find, analyze, and describe internal and external factors that contribute to the professional development of lecturers; alternative strategies and priorities for empowerment-based lecturer professional development strategies at State Islamic Religious Universities. This research is field research using the descriptive analytical method. Data was obtained from observations, literature studies, key informants, and experts. The results of this study indicate that; First, the ability of IAIN Palopo's internal factors is powerful and able to overcome its weaknesses in the professional development of lecturers. In addition, IAIN Palopo has a reasonably high opportunity and is very responsive in overcoming challenges in the professional development of lecturers. Second, several alternative strategies were formulated, leading to the implementation of an integration strategy through market penetration and product development (research, community service, and article writing) through collaboration with universities and other institutions both domestically and abroad, by empowering scientific consortiums lecturers and international center.